(untitled) (Research, Society and Development, 2022)
Introduction and objective: the present study assessed the knowledge of dentists and dental students about bisphosphonates and bisphosphonate-associated osteonecrosis of the jaws (BAONJ). Methodology: a survey was applied to dentists and dental students during dental meetings in the city of Rio de Janeiro/RJ, Brazil. Results were descriptively and comparatively analyzed using the SPSS program. Results: the final sample (n=308) was composed mostly by young adults, females (n=233; 76%) and 52% (n=159) were dental students. Most participants (n=185; 60%) were derived from private dental schools. From the total, 79% (n=243) of the participants told they had some information about bisphosphonates, 68% (n=209) recognized BAONJ as a possible side effect of their use, and 84% (n=259) considered important to ask about bisphosphonates use during anamnesis. Participants with more access to information, derived from public dental schools and graduate dentists demonstrated a higher understanding about the indications for bisphosphonates use, their action mechanism, BAONJ as an adverse effect, risk factors associated with the drugs, oral risk factors and oral care measures important to BAONJ risk reduction. Conclusions: there are several knowledge gaps on bisphosphonates and BAONJ and understanding these difficulties is important for the establishment of strategies of diffusion of the information and changing teaching models in dental schools, dental meetings and extension activities.